Introspection — One or More? Pluralism about Self-Knowledge - Komorowska-Mach, Joanna (Filozofia Nauki, 2019)
The aim of this paper is to provide a metaphilosophical analysis of the debate between monistic and pluralistic approaches to self-knowledge. I start by presenting the background for the discussion, clarifying the terminology, and drawing a distinction between moderate and radical pluralism. I then discuss and evaluate arguments for monism that appeal to general methodological guidelines as well as those relying on specific assumptions about the objects and character of self-knowledge. I offer a separate analysis of Eric Schwitzgebel’s radical pluralism, which threatens to undermine both monism and moderate pluralism. I close by describing a way of looking at the problem of the homogeneity of self-knowledge that goes beyond the monism–pluralism dichotomy and arguing that the heterogeneity and multidimensionality of the problem of self-knowledge are more important than the plurality of the solutions.